IL6-inhibitors in treatment of SARS COVID19 - Shcherbakov, Serhii; Mazurenko, Hanna; Yovenko, Ihor (ScienceRise: Medical Science, 2022)
The aim of this study was to evaluate the clinical efficacy and safety of a two-dose approach in the administration of tocilizumab in patients with SARS COVID19 Material and methods. The study was carried out on the basis of the Odrex Medical House in 2000-2021. The total sample included 4,112 patients hospitalized in a specialized department with coronavirus pneumonia. Of this sample, 150 patients were prescribed tocilizumab at a dose of 8 mg/kg of patient weight, including 36 (24.0 %) cases when tocilizumab was administered in a two-dose regimen. In the case of a two-dose regimen, the second dose was administered no earlier than 24 hours after the first one. All patients were examined according to the current clinical protocols. The hemogram, the content of CRP, ferritin, interleukin-6 were assessed. All patients received dexamethasone intramuscularly at a dose of at least 6 mg per day. Statistical processing was carried out by methods of analysis of variance using the software Statistica 13.0. Results. After the use of tocilizumab, the patients had a decrease in body temperature and a decrease in the need for oxygen support. At the same time, the normalization of indicators of the activity of the systemic inflammatory response was observed. Mortality after the use of tocilizumab was 29.3 %; in all cases, the deaths had an extremely severe course of coronavirus infection and a significant comorbid background. There were no manifestations of anaphylaxis and cases of secondary infection after the appointment of tocilizumab. Conclusions. The use of tocilizumab could significantly improve the condition of patients with SARS COVID19. There were no signs of anaphylaxis and cases of secondary infection after the administration of tocilizumab. In the absence of a pronounced clinical effect within 24 hours after the first dose of tocilizumab in patients with severe SARS COVID19, it is advisable to re-administer the drug (two-dose regimen)